PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, PERSEPSI TARIF PAJAK, DAN KEADILAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Pipit Annisa Fitria; Edy Supriyono (ECONBANK: Journal of Economics and Banking, 2019)
The purpose of this research is to find out the achievement factors of the tax compliance of Small and Medium Enterprise in Purbalingga Regency. The variables tested were the understanding of tax regulations, perceptions of tax rates, and tax justice. The population in this study were all tax payers for Small and Medium Micro Businesses in Purbalingga Regency. The samples produced in this study were 65 respondents. Selected respondents are Small and Medium Micro Businesses who already have an NPWP. The data were collected through questionnaires and analyzed using multiple linear regression analysis. Based on the t-test results show that the variable understanding of tax regulations has a positive effect on taxpayer compliance, the tax rate perception variable negatively affects taxpayer compliance, and the tax justice variable does not affect taxpayer compliance